2008
DOI: 10.4161/cc.7.21.6919
|View full text |Cite
|
Sign up to set email alerts
|

Growth stimulation leads to cellular senescence when the cell cycle is blocked

Abstract: We tested a hypothesis that activation of growth-promoting pathways is required for cellular senescence. In the presence of serum, induction of p21 caused senescence, characterized by betaGalactosidase staining, cell hypertrophy, increased levels of cyclin D1 and active TOR (target of rapamycin, also known as mTOR). Serum starvation and rapamycin inhibited TOR and prevented the expression of some senescent markers, despite high levels of p21 and cell cycle arrest. In the presence of serum, p21-arrested cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
420
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(441 citation statements)
references
References 22 publications
18
420
0
3
Order By: Relevance
“…This is consistent with doxorubicin-induced senescence in tumor cells (Chang et al, 1999) and primary fibroblasts (Baus et al, 2003;Demidenko and Blagosklonny, 2008).…”
Section: Resultssupporting
confidence: 81%
“…This is consistent with doxorubicin-induced senescence in tumor cells (Chang et al, 1999) and primary fibroblasts (Baus et al, 2003;Demidenko and Blagosklonny, 2008).…”
Section: Resultssupporting
confidence: 81%
“…Interestingly, similar finding occurred in HDF cells at 5 days, but in Huh7 cancer cells at 3 days, after treatment with H 2 O 2 . The more rapid response to actin regulating phenomenon in cancer cells may be accounted for by the fact that the more actively growing cells can reach cellular senescence earlier than that of the growth arrested cells [6]. Indeed, infection of retrovirus carrying H-ras double mutants can induce premature senescence of primary culture of HDF, compared with HDF cells infected with the control virus [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is accelerated by DNA damage and stresses, i.e. induced senescence, whereas inhibition of cell growth prevents cellular senescence when the cell cycle is blocked by DNA damage and p21 WAF1 [6]. We earlier reported that globular actin (G-actin) accumulates in nuclei of the replicatively senescent human diploid E X P E R I M E N T A L C E L L R E S E A R C H 3 1 7 ( 2 0 1 1 ) 9 4 1 -9 5 4 fibroblasts (HDF) and induced senescence of cancer cells by treatment with either H 2 O 2 , deferoxamine, TGF-β1 or over expression of H-Ras double mutants [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Recently these pathways have been shown to play critical roles in the preventing aging and senescence. [12][13][14][15][16] Thus these pathways have been targeted to promote longevity by altering the aging process which might be enhanced when these pathways are hyperactivated. these pathways is mediated by a series of kinases, phosphatases and various exchange proteins.…”
Section: Introductionmentioning
confidence: 99%